The burden of vitamin D deficiency in a mediterranean country without a policy of food fortification - Lippi, Giuseppe; Nouvenne, Antonio; Ticinesi, Andrea; Bonelli, Patrizia; Salvagno, Gian Luca; Cervellin, Gianfranco; Guidi, Gian Cesare (Acta Biomedica Atenei Parmensis, 2015)
Background: Vitamin D deficiency is a public healthcare issue and its correction is increasingly regarded as a cornerstone of preventive medicine. Methods: We designed a retrospective observational study to clearly define the burden of total vitamin D (25-hydroxyvitamin D) deficiency in a supposedly healthy population of outpatients residing in two regions (Emilia Romagna and Veneto) of Northern Italy. Results: 25-hydroxyvitamin D results were available for a total number of 5,096 outpatients in the two centers. The median value of 25-hydroxyvitamin D was 60 nmol/L, and was higher in women than in men (62 nmol/L versus 56 nmol/L; p<0.001). The rate of 25-hydroxyvitamin D deficiency was 36%, and was marginally but significantly higher in men than in women (40% versus 35%; p=0.003). A significant variation in the rate of 25-hydroxyvitamin D deficiency was found throughout different age ranges, exhibiting a significant increase in the elderly. Conclusions: The results of this large observational study show that the burden of 25-hydroxyvitamin D deficiency in two regions of a Mediterranean country without a policy of food fortification is as high as 36%, and this evidence represents a background for healthcare preventive measures aimed at reducing the prevalence of this condition in the general population. (www.actabiomedica.it)